2019
DOI: 10.1007/s11663-019-01752-4
|View full text |Cite
|
Sign up to set email alerts
|

MnS Precipitation Behavior of High-Sulfur Microalloyed Steel Under Sub-rapid Solidification Process

Abstract: A typical high-sulfur microalloyed steel was investigated by a sub-rapid solidification process for grain refinement of the as-cast microstructure. The size and distribution characteristics of the MnS precipitates were analyzed. The variations in the dendrite morphology and secondary dendrite arm spacing (SDAS) under different cooling rates have been studied, which strongly influence the precipitation behavior of MnS. The 3D-morphology of MnS precipitates was revealed by a novel saturated picric acid deep-etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Crystals tend to grow with facets, because this maximizes bond formation within a growth slice and therefore minimizes surface energy. [20,28] In addition, higher precipitation temperature and excessive precipitation amount of MnS in sulfur-containing steel are beneficial to the growth kinetics. As a result, more large-size MnS is observed in the sulfurcontaining 42CrMo steel due to the significant increasing of supersaturation during solidification and subsequent cooling process.…”
Section: Effect Of Sulfur Contents On Sulfide Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystals tend to grow with facets, because this maximizes bond formation within a growth slice and therefore minimizes surface energy. [20,28] In addition, higher precipitation temperature and excessive precipitation amount of MnS in sulfur-containing steel are beneficial to the growth kinetics. As a result, more large-size MnS is observed in the sulfurcontaining 42CrMo steel due to the significant increasing of supersaturation during solidification and subsequent cooling process.…”
Section: Effect Of Sulfur Contents On Sulfide Precipitationmentioning
confidence: 99%
“…[6] Thus, regarding the important role of MnS inclusions in steel, lots of investigations have been performed, especially, the mechanism of morphology evolution by optimizing cooling rates. [15][16][17][18][19][20][21][22][23] At present, according to the classic work by Sims et al, the MnS in an as-cast steel can be typically classified as follows: globular MnS (Type I); fine rodlike MnS (Type II); and angular MnS (Type III). [15,16] However, the mechanisms of morphology evolution by various cooling rates still remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing the cooling rate and introducing physical fields are the two common methods for controlling the MnS precipitation of steel. [9][10][11][12][13] It has been reported that MnS precipitates in the as-cast steel should have a mean length lower than 5lm for to obtain better machinability and mechanical properties. [9] Wang et al [10] found that the percentage of the large MnS with a length over 5lm decreased from 6.2 to 2.6 pct as the solidification condition changed from air cooling to sub-rapid.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] It has been reported that MnS precipitates in the as-cast steel should have a mean length lower than 5lm for to obtain better machinability and mechanical properties. [9] Wang et al [10] found that the percentage of the large MnS with a length over 5lm decreased from 6.2 to 2.6 pct as the solidification condition changed from air cooling to sub-rapid. Zhang et al [5] revealed that electro-pulsing enabled the separation of MnS inclusions from molten steel according to the differences in electrical properties between the inclusions and liquid metal.…”
Section: Introductionmentioning
confidence: 99%